2020
DOI: 10.1007/s11096-020-00972-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the clinical pharmacist-led interventions in China: A systematic review and Meta-Analysis

Abstract: Background The clinical pharmacist has been an important partner in clinical treatment team. In China, there is no systematic review to evaluate the effectiveness of clinical pharmacy services on patients' outcomes such as hospitalization days, readmission rate and mortality. Aim of the review To investigate the impact of clinical pharmacist services on patients' length of hospitalization, readmission and mortality in China. Methods A literature search was performed in PubMed, EMBASE, Cochrane Library, clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…20 A meta-analysis conducted by Qin et al showed that type of disease and type of pharmacist intervention impact the effectiveness of clinical pharmacist intervention. 21 Limitations of this study were the variety of clinical pharmacist's competency and the lack of study period.…”
Section: Discussionmentioning
confidence: 95%
“…20 A meta-analysis conducted by Qin et al showed that type of disease and type of pharmacist intervention impact the effectiveness of clinical pharmacist intervention. 21 Limitations of this study were the variety of clinical pharmacist's competency and the lack of study period.…”
Section: Discussionmentioning
confidence: 95%
“…In China, pharmaceutical services developed rapidly recent years since the Chinese Ministry of Health firstly proposed to establish a clinical pharmacist system in hospitals in 2002 (11). A recent systematic review has shown that in China, the pharmacistled intervention could significantly reduce the length of hospitalization, readmission rate and mortality during hospital of patients (12). Due to the personal shortage in majority of hospitals, it is unrealistic to apply personalcentered pharmaceutical services to all patients (13).…”
Section: Role Of Clinical Pharmacistsmentioning
confidence: 99%
“…Pharmacy Practice 2022 Jul-Sep;20(3):2708. https://doi.org/10.18549/PharmPract.2022.3.2708 2 hospitalized patients as well as reductions in hospital readmissions. [4][5][6][7][8][9] Disagreement between health care providers on medicationrelated problems or pharmaceutical interventions can lead to several adverse clinical outcomes, including; sub-optimal treatment, drug toxicities or increased overall healthcare cost. 10,11 A more recent study, showed poor overall agreement on the severity of clinical pharmacist interventions by other different health care providers in the team.…”
Section: Introductionmentioning
confidence: 99%